Evaluation of estrogen receptor alpha activation by glyphosate-based herbicide constituents. (October 2017) - Mesnage, Robin; Phedonos, Alexia; Biserni, Martina; Arno, Matthew; Balu, Sucharitha; Corton, J. Christopher; Ugarte, Ricardo; Antoniou, Michael N.
Abstract: The safety, including the endocrine disruptive capability, of glyphosate-based herbicides (GBHs) is a matter of intense debate. We evaluated the estrogenic potential of glyphosate, commercial GBHs and polyethoxylated tallowamine adjuvants present as co-formulants in GBHs. Glyphosate (≥10, 000 μg/L or 59 μM) promoted proliferation of estrogen-dependent MCF-7 human breast cancer cells. Glyphosate also increased the expression of an estrogen response element-luciferase reporter gene (ERE-luc) in T47D-KBluc cells, which was blocked by the estrogen antagonist ICI 182, 780. Commercial GBH formulations or their adjuvants alone did not exhibit estrogenic effects in either assay. Transcriptomics analysis of MCF-7 cells treated with glyphosate revealed changes in gene expression reflective of hormone-induced cell proliferation but did not overlap with an ERα gene expression biomarker. Calculation of glyphosate binding energy to ERα predicts a weak and unstable interaction (−4.10 kcal mol −1 ) compared to estradiol (−25.79 kcal mol −1 ), which suggests that activation of this receptor by glyphosate is via a ligand-independent mechanism. Induction of ERE-luc expression by the PKA signalling activator IBMX shows that ERE-luc is responsive to ligand-independent activation, suggesting a possible mechanism of glyphosate-mediated activation. Our study reveals that glyphosate, but not other components present in GBHs, can activate ERα in vitro, albeit at relatively high concentrations. Highlights: We evaluated the estrogenic potential of glyphosate-based herbicide constituents. Glyphosate but not other components present in 4 major commercial formulations activate ERα. Transcriptome profiles reflected proliferative effects, but did not overlap with that of an ERα gene expression biomarker. Molecular dynamics simulations show that glyphosate is unlikely to bind to ERα. Activation of ERα by glyphosate could be via a ligand-independent mechanism.